Assessment of resistance and susceptibility in Culex quinquefasciatus larvae exposed to conventional and novel insecticides (Zoo Botanica, 2025)
Mosquitoes belong to the order Diptera, suborder Nematocera, and family Culicidae. Culex quinquefasciatus Say is a medically significant mosquito and major pest species with a global distribution. The indiscriminate use of pesticides leads to environmental issues such as health risks, disruption of natural predators, ecosystem imbalances, and the development of resistance in insect pests. Therefore, the present study aimed to reduce the excessive use of pesticides by exploring novel alternative and chemical insecticides. The susceptibility (%) and resistance (%) of third instar larvae of Culex quinquefasciatus to conventional chemicals (lambda-cyhalothrin, permethrin and deltamethrin) and new chemicals (spinosad, ivermectin, and emamectin benzoate) were determined using different concentration rates (100, 125 and 150 ppm) and exposure times (24, 48, 72 h). In general, exposure time did not significantly affect the susceptibility or resistance percentages of Culex quinquefasciatus. However, changes in concentration directly influenced both susceptibility and resistance to both conventional and new chemicals. Lambda-cyhalothrin had the highest LD50 value (1.80), whereas spinosad had the lowest LD50 value (0.03). The LD90 value was highest for deltamethrin, whereas spinosad exhibited the lowest LD90 value across all treatments.
Keywords: Culex quinquefasciatus; insecticides; resistance; susceptibility; Lambda-cyhalothrin